Comparative Politics, Political Settlements, and the Political Economy of Health Financing Reform; Comment on "Health Coverage and Financial Protection in Uganda: A Political Economy Perspective" - Kevin Croke (Kerman University of Medical Sciences, 2023)
Nannini et al analyze barriers to national health insurance reforms in Uganda using a political economy approach primarily rooted in stakeholder analysis. This approach is valuable, not only for its clear description of the interestbased politics at play, but also for its extension of stakeholder analysis to include consideration of the role of ideas and institutions in the policy process. However this analysis, and others like it, could be further strengthened by adding insights from two different sources. The first is the comparative politics literature on the Ugandan regime. The second is a related approach which analyzes public service delivery in the context of a country's underlying "political settlement." Stakeholder-based approaches to health financing reform emphasize interest group conflict about the contents of policy reforms. By contrast, these complementary approaches imply distinct barriers to successful implementation of national health insurance in Uganda, rooted in the regime's de-industrialization and the personalization of politics and resource allocation. They also suggest possible leverage points or avenues for progress which differ from those suggested by stakeholder analysis.